Studying the Relationship Between Organizational Learning and Organizational Commitment of Staffs of Well-Being Organization in Yazd Province - Mohammad Kamali; Shabnam Asadollahi; Mahnaz Afshari; Hosein Mobaraki; Nasrin Sherbaf (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Since disabled persons and their families are those who refer to wellbeing organization, staff of such organization requires special education to provide essential capabilities in them. On the other hand, such educations should increase job satisfaction of staff leading to the increasing commitment. The current research aims to find the relation between organizational learning and organizational commitment of staff in wellbeing organization of Yazd province. Methods: This is an analytical-descriptive research and the statistical population is all staff of wellbeing organization of Yazd province (74 persons). Sampling was done by census in 2015. To gather information, Nifa organizational learning questionnaire and Allen & Mayer's organizational commitment questionnaire were used and each includes 24 items. Data were analyzed using SPSS18 software, t-test, ANOVA, Pearson correlation and linear regression tests in significance level of P-value < 0.05. Results: Participants were 34 men (46%) and 40 women (54%). 66% of respondents had bachelor and 35.1% had work experience between 11 and 15 years. There was no significant difference between organizational commitment, organizational learning and gender. There was no significant relation between age and other research variables except for normative commitment. There was a linear significant relation and positive and direct correlation between components of organizational commitment including affective commitment, continuous commitment and normative commitment (P-value < 0.01). Conclusion: there was a positive and direct relation between organizational learning and organizational commitment of staff. Organizational commitment and organizational learning were averagely low in the organization. Therefore, managers of wellbeing organization should identify educational requirements of staff and offer opportunities to meet such needs and to promote abilities, skills, loyalty and commitment of staff to the organization.